PERAN PROTOKOLER DALAM MENUNJANG KEBERHASILAN KINERJA KEPALA BAGIAN UMUM PEMERINTAHAN KABUPATEN DELI SERDANG - Lubis, Endang (Universitas Medan Area, 2015)
In improving performance in each unit of the bureaucracy, local governments require various approaches to boost the performance of the organizational unit to another organizational unit. This study aims to look at how the protocol role in the success of the performance of the head of the public administration Deli Serdang. The method used manifold qualitative study with a descriptive approach, the source of the data in this study derived from the literature and in-depth interviews. Research results generally indicate a role in supporting the protocol has a maximum performance of the head of the public administration Deli Serdang.